Motivation of People with HIV/AIDS in Terms of Sports Activities - Megia Erida; Arisman Arisman (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to determine the motivation of people with HIV / AIDS in terms of futsal sports activities at Rumah Cemara Bandung. The research was carried out using the descriptive survey method. Sampling in this study used incidental sampling techniques. The sample in this study was 1 person who was positive for HIV/AIDS. The instrument used is in the form of a closed questionnaire using a Likert Scale. Based on the validity test of valid questionnaires, there were 29 questions out of 41 statement questions. The Reliability Test obtained 0.767 and falls under the criteria of high reliability. Data processing obtained a percentage of physiological needs of 37.5%, the need for a sense of security of 16.7%, social needs of 100%, appreciation needs of 33.3% and self-actualization needs of 100%. Thus, researchers can conclude that the motivation of people with HIV / AIDS in terms of the aspect of physiological needs in the criteria of motivation is very low, the aspect of the need for a sense of security is critiqued very low motivation, the aspect of social needs is critiqued very high motivation, the aspect of appreciation needs is critiqued very low and the aspect of self-actualization needs is critied very high.